2016
DOI: 10.1038/srep20243
|View full text |Cite|
|
Sign up to set email alerts
|

Corneal Power, Anterior Segment Length and Lens Power in 14-year-old Chinese Children: the Anyang Childhood Eye Study

Abstract: To analyze the components of young Chinese eyes with special attention to differences in corneal power, anterior segment length and lens power. Cycloplegic refractions and ocular biometry with LENSTAR were used to calculate lens power with Bennett’s method. Mean refraction and mean values for the ocular components of five different refractive groups were studied with ANOVA and post-hoc Scheffé tests. There were 1889 subjects included with full data of refraction and ocular components. As expected, mean axial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 31 publications
14
27
0
Order By: Relevance
“…Our study showed higher LP and in girls than boys (unstandardised regression coefficient: 0.016). This difference has also been reported by Iribarren et al .,3 Li et al 18 and Twelker et al 8. Nevertheless, it should be noted that this difference is not influenced by other ocular components because their effects were controlled in the regression model.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our study showed higher LP and in girls than boys (unstandardised regression coefficient: 0.016). This difference has also been reported by Iribarren et al .,3 Li et al 18 and Twelker et al 8. Nevertheless, it should be noted that this difference is not influenced by other ocular components because their effects were controlled in the regression model.…”
Section: Discussionsupporting
confidence: 80%
“…According to our findings, the highest and lowest LP was seen in hyperopic and myopic children, respectively; although Jones et al ,11 Li et al 18 and Iribarren et al 3 reported similar findings in children, Olsen19 reported a different finding in adults. Nonetheless, the LP decreased in myopic, hyperopic and emmetropic children with age.…”
Section: Discussionsupporting
confidence: 61%
“…1,12,13 We found in our study that female students with high myopia had shorter mean average corneal curvature, similar to Li et al, but females without refractive errors had slightly higher mean average corneal curvature than males in another study. 13,14 A result similar to a study done by Iyamu and Osuobeni were they found that age and gender did not affect corneal curvature in emmetropes, however we only found a significant effect with gender on the corneal curvature of the young undergraduates with high myopia. 13 Our study is also in agreement with a previous study that there was no significant mean differences (P>0.05) between the various degrees of high myopia.…”
Section: Discussionsupporting
confidence: 90%
“…The significant difference in IOP between genders, the lower pressure found in both male and female hyperopes than in myopes (figure 1C), and the lower pressure found in eyes with lower myopic refractive error at baseline (figure 1D) are difficult to explain. Girls and hyperopes are known to have smaller anterior segments,11 so it is not clear why girls have higher pressure and hyperopes lower pressure. More research in this area is warranted.…”
Section: Discussionmentioning
confidence: 99%